Review projecting shikonin as a therapeutic candidate in female carcinomas: a preclinical perspective - Pandey, Pratibha; Lakhanpal, Sorabh; Jamuna, K. V.; Singh, Ajay; Abohassan, Mohammad; Park, Moon Nyeo; Shin, Sang-Won; Kang, Han Na; Zahera, Manaal; Saeed, Mohd; Khan, Fahad; Kim, Bonglee (Frontiers in Pharmacology, 2025)
Bioactive substances, especially shikonin (naphthoquinone), which is extracted from Lithospermum erythrorhizon, have drawn much attention as promising substitutes for preventing cancer malignancy. Shikonin (SK) has displayed a broad spectrum of anticancer activities, such as necroptosis, cell cycle invasion, Autophagy, apoptosis, Diabetes, DNA damage induction, and suppression of angiogenesis. It reverses drug resistance and inhibited cancer cell growth by altering their metabolism. According to preliminary clinical trials, shikonin may improve the effectiveness of known chemotherapeutic drugs, radiation therapies, and immunotherapies through synergistic and additive interactions in female carcinomas. Despite its potential, additional investigation is required to pinpoint exact processes by which shikonin causes metabolic reprogramming in female cancers. While numerous researches have been reported to understanding the anticancer potential of shikonin, more research is needed to investigate its synergistic effects with conventional cancer therapies and assessing its clinical efficacy in robust trials. Due to less clinical data, more number of clinical trials is vital to establish their efficacy and safety in human patients, while mechanistic experimentation could unveil new therapeutic oncotargets in managing female carcinomas.